African Somaesthetics: Cultures, Feminisms, Politics - Botha, Catherine F. (Studies in Somaesthetics, 2021)
In African Somaesthetics: Cultures, Feminisms, Politics, Catherine F. Botha brings together original research on the body in African cultures, specifically interrogating the possibilities of the contribution of a somaesthetic approach in the context of colonization, decolonization, and globalization in Africa. The eleven innovative contributions that consider the somaesthetic dimensions of experience in the context of Africa (centred broadly around the themes of politics, feminisms, and cultures) reflect a diversity of perspectives and positions. The book is a first of its kind in gathering together novel and focused analyses of the body as conceived of from an African perspective.